Osteoblastogenic activity of ark shell protein hydrolysates with low molecular weight in mouse mesenchymal stem cells. Issue 35 (21st March 2016) - Hyung, Jun-Ho; Ahn, Chang-Bum; Je, Jae-Young
Abstract : Ark shell protein promotes bone formation through regulating osteoblast differentiation. Abstract : Aging of human bone is characterized by decreased bone formation and bone mass. In this study, ark shell protein hydrolysates (ASPHs) were prepared by peptic hydrolysis with optimal conditions and were fractionated into 3–10 kDa, 1–3 kDa and <1 kDa fractions. Modulating the effects of ASPH with low molecular weight (ASPH < 1 kDa), which exhibited the highest stimulation effect on alkaline phosphatase (ALP) activity in mouse mesenchymal stem cells (MSCs), was investigated by measuring osteogenic biomarkers including bone morphogenetic protein-2 (BMP-2), p-Smad1/5, Runx2, Dlx5, osterix, and MAPKs as well as ALP activity, type I collagen, mineralization and osteocalcin. Treatment with ASPH < 1 kDa significantly increased the expressions of osteogenic biomarkers and also up-regulated ALP activity, mineralization, type I collagen and osteocalcin in MSCs. This study may provide new insights in the osteoblastic differentiation and ASPH < 1 kDa may be useful for health-promoting functional food ingredients against osteoporosis.